Testing bioformulation of Chaetomium elatum ChE01 to control Fusarium wilt of tomato - Soytong, K. (International Journal of Agricultural Technology, 2015)
The research findings on tomato wilt collected from infested fields resulted to isolate and identify the causal agent as Fusarium oxysporum f. sp. lycopersici according to morphological and molecular phylogeny. Bioactivities tests of crude extracts and pure compounds were proved as a control mechanism. All tested crude extracts of Ch. elatum ChE01 was significantly inhibited conidia production of F. oxysporum f. sp. lycopersici. With hexane crude extract at ED50 of 0.65 µg/ml and EtOAC crude extract at ED50 of 3.39 µg/ml. It is clearly demonstrated that chaetoglobosin-C, a pure compound produced by Ch. elatum ChE01 significantly inhibited conidial production of F. oxysporum f. sp. Lycopersici at ED50 of 5.94 µg/ml. Chaetoglobosin-C is expressed as a antibiotic substances to destroy the pathogen cells implies antibiosis. Inocula of F. oxysporum f. sp. lycopersici (1 × 107 spores/ml) were mixed with chaetoglobosin-C and inoculated to tomato seedlings caused no symptoms at day 21 while the treatment with pathogen alone showed significantly highest disease severity index. Withthis, no wilt incidences were appeared at all tested concentration of 10, 50 and 100 μg/ml of chaetoglobosin-C. It is stated that chaetoglobosin-C affected directly to the pathogen inocula implies antibiosis which the occurrences of ruptured cells and abnormal conidia of pathogen. Ch. elatum ChE01 was formulated as powder bioformulations gave a good result to control wilt of tomato var Sida caused by F. oxysporumf.sp. lycopersici. The treated tomatoes showed the lowest wilt incidence in oil and powder bioformulations from Ch. elatum ChE01 which significantly differed from Prochoraz and inoculated control. Based on the result, oil bioformulation from Ch. elatum ChE01 gave significantly better plant parameters in terms of plant height, plant weight, root weight, number of fruits and fruit weight than powder bioformulation and Prochoraz when compared to the inoculated control with F. oxysporum f. sp lycopersici. It is suggested that this new reports of bioformulation of Ch. elatum ChE01 could be used as further biofungicide to control tomato wilt caused by F. oxysporum f.sp. lycopersici.